How did you perform? Investigating football players’ perception of self-regulated passing performances under auditory noise environments - Klatt, Stefanie; Otte, Fabian Werner; Beavan, Adam; Schumacher, Tom; Millar, Sarah Kate (Frontiers in Psychology, 2024)
This paper deals with the question on how sport performances may be influenced by internal, emotional processes, which stem from outside feedback. In terms of methods, players’ subjective performance ratings for four experimental auditory cue conditions were examined; these included both ‘positive’ and ‘negative’ stadium noise, ‘no (auditory) conditions’, and a control/‘baseline’ condition. This resulted in a qualitative-analytic data set that was obtained succeeding each auditory cue condition using a unique football training machine (i.e., known as ‘Footbonaut’). Without having received any coaching/performance feedback, players were asked to rate and individually comment on their perceived performance ratings for each experimental auditory condition. Findings indicate stronger and more significant correlations between auditory conditions and subjective ratings compared to the non-auditory condition and its subjective rating. Furthermore, data provides initial insight into players’ emotional experiences during each of the practice conditions. These noteworthy findings on players’ abilities to accurately judge their performances based on self-monitoring and intrinsic feedback are discussed from an Ecological Dynamics perspective, linked to a Nonlinear Pedagogy for coaching. Here, representative and affective learning designs for skill learning and performance preparation are presented. Finally, a hypothetical catalyst effect of auditory stadium noise on subjective performance rating is proposed.